1989
DOI: 10.1002/cber.19891220512
|View full text |Cite
|
Sign up to set email alerts
|

Blei(II)‐Verbindungen mit π‐gebundenen Pentamethylcyclopentadienylliganden – Synthesen, Strukturen und Bindungsverhältnisse

Abstract: Chem. Ber. 122 (1989) [865][866][867][868][869][870] Die in Tab

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
1
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 14 publications
3
32
1
2
Order By: Relevance
“…[11,15,18,20,21,23] For the heaviest Group 14 elements, tin and lead, work had been focused primarily on derivatized cyclopentadienyl half-sandwich complexes, where the metal cation is h 5 bonded to five carbon atoms of the cyclopentadienyl ring. [1][2][3]17] Parallel, recent work has shown that bulky terphenyl ligands can stablize a range of lowcoordinate neutral and anionic species with unusual or previously unknown bonding. [27] We were therefore anxious to test the effectiveness of these useful monodentate ligands in stabilizing cationic Group 14 species with unusually low coordination numbers.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…[11,15,18,20,21,23] For the heaviest Group 14 elements, tin and lead, work had been focused primarily on derivatized cyclopentadienyl half-sandwich complexes, where the metal cation is h 5 bonded to five carbon atoms of the cyclopentadienyl ring. [1][2][3]17] Parallel, recent work has shown that bulky terphenyl ligands can stablize a range of lowcoordinate neutral and anionic species with unusual or previously unknown bonding. [27] We were therefore anxious to test the effectiveness of these useful monodentate ligands in stabilizing cationic Group 14 species with unusually low coordination numbers.…”
mentioning
confidence: 97%
“…X-ray quality crystals of 2 were isolated after recrystallization from hexane. [30] The structure of 2 ( Figure 3 , [1] which range from 2.512 to 2.598 . The PbÀ centroid length for [(h 5 -C 5 Me 5 )Pb] + was found to be near 2.27 .…”
mentioning
confidence: 99%
“…There has been intense, recent interest in the synthesis and properties of heavier Group‐14‐element (Si–Pb) analogues of carbocations 126. However, they have proven difficult to isolate in the absence of stabilization by further coordination of the Group 14 element.…”
mentioning
confidence: 99%
“…To date, no one cyclopentadienyl ligand has been structurally characterised as a half‐sandwich derivative for all three heavy group 14 elements, Ge, Sn and Pb. Furthermore, no isostructural derivatives have been characterised: in [E(η‐Cp*)(BF 4 )], for example, where E = Sn,22 a monomeric structure is observed but where E = Pb,29 a dimer, where the two BF 4 units bridge the two Pb centres and the Cp* ligands are terminal, is observed. For the Cp s ligand, where E = Ge, Sn or Pb, an isostructural series of tetramers is observed 4.…”
Section: Cyclopentadienyl Derivativesmentioning
confidence: 99%